Dissecting the membrane lipid binding properties and lipase activity of Mycobacterium tuberculosis LipY domains. (16th May 2019) - Santucci, Pierre; Smichi, Nabil; Diomandé, Sadia; Poncin, Isabelle; Point, Vanessa; Gaussier, Hélène; Cavalier, Jean‐François; Kremer, Laurent; Canaan, Stéphane
Abstract : The Mycobacterium tuberculosis LipY protein, a prototype of the proline‐glutamic acid (PE) family, exhibits a triacylglycerol (TAG) hydrolase activity that contributes to host cell lipid degradation and persistence of the bacilli. LipY is found either as a full‐length intracytosolic form or as a mature extracellular form lacking the N‐terminal PE domain. Even though the contribution of the extracellular form in TAG consumption has been partly elucidated, very little information is available regarding the potential interactions of either full‐length LipY with the cytoplasmic membrane, or mature form LipY with the outer membrane. Herein, several LipY variants truncated in their N‐terminal domain were produced and biochemically characterized in lipid–protein interaction assays, using the monomolecular film technique and FTIR. Comparison of the catalytic activities of these recombinant proteins showed that LipY∆149, corresponding to the extracellular form of LipY lacking the PE domain, is more active than the full‐length protein. This confirms previous studies reporting that the PE domain negatively modulates the TAG hydrolase activity of LipY. Lipid–protein interaction studies indicate that the PE domain anchors LipY onto membrane lipids. Consistent with these findings, we show that LipY∆149 is loosely associated with the mycobacterial cell wall, and that this interaction is mediated by the sole lipase domain. Overall, our results bring new information regarding the molecular mechanisms by which LipY either binds and hydrolyses host cell lipids or degrades TAG, the major source of lipids within mycobacterial intracytosolic lipid inclusions. Abstract : Here, we present a complete biochemical study of LipY, the major M. tuberculosis triacylglycerol (TAG)‐lipase that contributes to host cell lipid degradation and persistence of the bacilli. We describe interaction studies of the full‐length intracytosolic form of LipY vs the mature extracellular form lacking the N‐terminal PE domain. Our results provide insight into the molecular mechanisms by which LipY either binds and hydrolyses host cell lipids or degrades TAG.